Proses Penerbitan Dokumen Port Health Quarantine Clearance (PHQC) Kesehatan Kapal pada Balai Kekarantinaan Kesehatan Kelas I oleh PT. Tarunacipta Kencana Cabang Dumai - Robinaria Nainggolan; Fadiyah Hani Sabila (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
The process of issuing the Port Health Quarantine Clearance (PHQC) document for vessel health at the Class I Quarantine Health Office by PT. TarunaCipta Kencana Dumai Branch ensures that every ship entering a port is in a healthy condition, free from diseases and pests. The issuance of the vessel health document is handled by the Quarantine Health Office. Before docking at Dumai port, PT. TarunaCipta Kencana acts as an agency representing the ship owner/principal in handling all matters related to the vessel’s interests. The company can also appoint other sub-agents to serve other vessels. PT. TarunaCipta Kencana Dumai Branch collaborates with various related agencies at Dumai port, providing services for the ship and crew (ABK) before, during, and after docking. The issuance of the vessel health quarantine document begins with a submission by the agent to the Quarantine Health Office (BKK), followed by an inspection by health officers, and finally issuing the Certificate of Free Pratique (COP) and PHQC. The data collection methods used were Field Research and Library Research, ensuring that the process of issuing PHQC documents adheres to established procedures.